The Relationship Between Fears of Compassion, Emotion Regulation Difficulties, and Emotional Eating in College Students: A Moderated Mediation Model - Zhang, Shuwei; Guo, Mingchun; Wang, Jingyun; Lin, Lihua (Frontiers in Psychology, 2021)
Although previous research has found the impact of fears of compassion on eating disorders, the mechanism underlying the relationship between fears of compassion and emotional eating remains to be examined. This study aimed to examine the mediating role of emotion regulation difficulties in the relationships between fears of compassion and emotional eating in college students, as well as the gender difference in the mediation model. The Fears of Compassion Scale, Difficulties in Emotion Regulation Scale and Dutch Eating Behavior Questionnaire were completed by 673 college students in Fujian Province, China. Structural Equation Modelling was primarily employed to analyze the data. The results showed that both fear of compassion for self and fear of compassion from others were positively associated with emotion regulation difficulties, which in turn were related to emotional eating for female college students. Emotion regulation difficulties played a significant mediating effect in the relationship between fears of compassion and emotional eating. Comparatively, for male college students, only fear of compassion for self was positively associated with emotion regulation difficulties, but emotion regulation difficulties were not related to emotion eating. Moreover, the mediating effect of emotion regulation difficulties was not significant in the relationship between fears of compassion and emotion eating for male college students. The findings suggest that it is important to improve individuals’ fears of compassion to reduce emotional eating, particularly for female college students.